Biomarker‐guided clinical development of the first‐in‐class anti‐inflammatory FPR2/ALX agonist ACT‐389949. (15th November 2016) - Stalder, Anna K.; Lott, Dominik; Strasser, Daniel S.; Cruz, Hans G.; Krause, Andreas; Groenen, Peter M.A.; Dingemanse, Jasper
Abstract : Aims: The main objectives of these two phase I studies were to investigate safety and tolerability as well as the pharmacokinetic/pharmacodynamic profile of the novel potent and selective formyl peptide receptor type 2 (FPR2)/Lipoxin A4 receptor (ALX) agonist ACT‐389949. A challenge model was used to assess the drug's anti‐inflammatory potential, with the aim of selecting a dosing regimen for future patient studies. Methods: Two double‐blind, randomized phase I studies investigated the safety, tolerability, pharmacokinetics and pharmacodynamics of ACT‐389949 at different doses and dosing regimens. Drug exposure was correlated with target engagement markers such as receptor internalization and cytokine measurements. The effect of FPR2/ALX agonism on neutrophil migration was studied in a lipopolysaccharide (LPS) inhalation model. Results: ACT‐389949 was well tolerated. Maximum concentrations were reached around 2 h after dosing, with a mean terminal half‐life of 29.3 h [95% confidence interval (CI) 25.5, 33.7]. After multiple‐dose administration, exposure increased by 111% (95% CI 89, 136), indicating drug accumulation. Administration of ACT‐389949 resulted in a dose‐dependent, long‐lasting internalization of FPR2/ALX into leukocytes. Pro‐ and anti‐inflammatory cytokines were dose‐dependently but transiently upregulated only after the first dose. No pharmacological effect on neutrophil count was observed in the LPS challenge test performed at steady state. Conclusions: FPR2/ALX agonism with ACT‐389949 was shown to be safe and well tolerated in healthy subjects. Receptor internalization and downstream mediators pointed towards a desensitization of the system, which may explain the lack of effect on neutrophil recruitment in the LPS challenge model.